Financing loss and damage: reviewing options under the Warsaw International Mechanism. (14th September 2018) - Gewirtzman, Jonathan; Natson, Sujay; Richards, Julie-Anne; Hoffmeister, Victoria; Durand, Alexis; Weikmans, Romain; Huq, Saleemul; Roberts, J. Timmons
ABSTRACT: After decades of pressure from vulnerable developing countries, the Warsaw International Mechanism on Loss and Damage (the WIM) was established at the nineteenth Conference of the Parties (COP 19) in 2013 to address costly damages from climate change. However, little progress has been made towards establishing a mechanism to fund loss and damage. The WIM's Executive Committee issued its first two-year workplan the following year at COP 20 which offered, among other things, a range of approaches to financing loss and damage programmes, which we review here. We provide brief overviews of each mechanism proposed by the WIM ExCom, describe their current applications, their statuses under the United Nations Framework Convention on Climate Change (UNFCCC), some of their advantages and disadvantages, and their current or potential application to loss and damage. We find that several of these mechanisms may be useful in supporting loss and damage programmes, but identify some key gaps. First, most of the mechanisms identified by the WIM ExCom are insurance schemes subsidized with voluntary contributions, which may not be adequate or reliable over time. Second, none were devised to apply to slow-onset events, or to non-economic losses and damages. That is, if harms are inflicted on parts of a society or its ecosystems that have no price, or if they occur gradually, they would probably not be covered by these mechanisms. Finally, the lack of a dedicated and adequate flow of finance to address the real loss and damage being experienced by vulnerable nations will require the use of innovative financial tools beyond those mentioned in the WIM ExCom workplan. Key policy insights Despite a full article of the 2015 Paris Agreement devoted to loss and damage, there is little international agreement on the scope of loss and damage programmes, and especially how they would be funded and by whom. Most of the loss and damage funding mechanisms identified by the WIM ExCom are insurance schemes subsidized with voluntary contributions, which may burden the most vulnerable countries and may not be reliable over time. None of the mechanisms were devised to apply to slow-onset events, or to non-economic losses and damages.